2020
DOI: 10.1007/s00276-020-02441-7
|View full text |Cite|
|
Sign up to set email alerts
|

Three-dimensional topography of scapular nutrient foramina

Abstract: The aim of this study is to describe the number and location of the nutrient foramina in human scapulae which can minimize blood loss during surgery. Methods 30 cadaveric scapulae were macerated to denude the skeletal tissue. The nutrient foramina of 0.51 mm and larger were identified and labeled by adhering glass beads. CT scans of these scapulae were segmented resulting in a surface model of each scapula and the location of the labeled nutrient foramina. All scapulae were scaled to the same size projecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…During ossi cation, this nutrient foramen is located in the growth center [24] and its presence is almost constant [10,20]. Our nding of 81% is comparable to that reported by Kalný [20], who recorded it in 82% of the group of 100 scapulae and to Donders´ nding [10] of 87% in a group of 30 specimens.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…During ossi cation, this nutrient foramen is located in the growth center [24] and its presence is almost constant [10,20]. Our nding of 81% is comparable to that reported by Kalný [20], who recorded it in 82% of the group of 100 scapulae and to Donders´ nding [10] of 87% in a group of 30 specimens.…”
Section: Discussionsupporting
confidence: 84%
“…The proximal, ascending branch travels to the nutrient foramen at the scapular spina base and then to the spinoglenoid notch where it anastomoses with the suprascapular artery [12,27]. During ossi cation, this nutrient foramen is located in the growth center [24] and its presence is almost constant [10,20]. Our nding of 81% is comparable to that reported by Kalný [20], who recorded it in 82% of the group of 100 scapulae and to Donders´ nding [10] of 87% in a group of 30 specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Most nutrient foramina however were found in the supraspinous fossa (29.7%) and were least present in the peri-glenoid area (17.7%). The presence of a nutrient canal in the glenoid region in this patient cannot be ruled out [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the location and number of nutrient foramina in various bones using macroscopic evaluation ( 6 – 10 ) and three-dimensional (3D) computed tomography (CT) measurement ( 11 , 12 ). Because the bone surface is irregular, there is still no uniform location for the nutrient foramina in the proximal femur.…”
Section: Introductionmentioning
confidence: 99%